Analysis of Covariance with Qualitative Data - Chamberlain, Gary (Review of Economic Studies, 1980)
Journal Article Analysis of Covariance with Qualitative Data Get access Gary Chamberlain Gary Chamberlain University of Wisconsin—Madison Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 1, 1980, Pages 225–238, https://doi.org/10.2307/2297110 Published: 01 January 1980